Contemporary Solutions to the Importance of Vitamin D in the Prevention of Osteoporosis in Postmenopausal Women - Nusratoy, Ochilova (Journal of Science in Medicine and Life, 2024)
The review provides information on vitamin D requirements for normal bone mineralization, phosphorus-calcium and bone metabolism, as well as the pleiotropic effects of D-hormone; the methods of laboratory examination of vitamin D in blood serum are described, the norm, deficiency and deficiency criteria of vitamin D in the human body are given. The role of drugs for the treatment of osteoporosis and mainly vitamin D in complex treatment was analyzed in elderly patients with decreased bone mineral density (BMD) and microarchitectural disturbances. According to the results of the study, a combination of 70 mg of alendronic acid and 5600 IU of cholecalciferol in one tablet (Fosavance® forte) was shown to be acceptable in the majority of patients with a moderate intake of calcium from food without additional calcium supplements. The antiresorptive effect of alendronic acid and the sufficient amount of vitamin D contribute to the faster conversion of vitamin D to D-hormone and to a significant increase in the fractional absorption of calcium from the small intestine. Once-weekly use of Fosavance Forte is more effective in normalizing vitamin D levels and, in combination with calcium and vitamin D supplementation, leads to statistically significant increases in spine and hip BMD compared to conventional osteoporosis therapy. It is paid for the safety of medication use, in particular, the rare adverse events, as well as the possibility of prescribing therapy for osteoporosis immediately after a fracture. The achievements of modern medicine in the field of treatment and prevention of infectious diseases (use of antibiotics, vaccination), medical examination and prevention programs, as well as significantly increasing the level of surgical support for urgent and planned operations have increased significantly. population life expectancy, especially in developed countries [1, 2]. The growing number of elderly people in the population presents a new challenge to medicine: to maintain their activity, independence and quality of life as much as possible.